Functional Alterations of White Matter in Chronic Never‐Treated and Treated Schizophrenia Patients. Issue 3 (20th December 2019) - Yang, Chengmin; Zhang, Wenjing; Yao, Li; Liu, Naici; Shah, Chandan; Zeng, Jiaxin; Yang, Zhipeng; Gong, Qiyong; Lui, Su
Abstract : Background: Schizophrenia is one of the most severe psychiatric disorders and dysfunction of gray matter (GM) has been usually investigated by resting‐state functional (f)MRI. However, functional organization of white matter (WM) in chronic schizophrenia remains unclear. Purpose: To investigate the WM functional alterations in chronic never‐treated schizophrenia and the effects of long‐term antipsychotic treatment. Study Type: Prospective. Subjects: Twenty‐five never‐treated, 41 matched antipsychotic‐treated schizophrenia, and 25 healthy comparison subjects. Field Strength/Sequence: Resting state (rs)‐fMRI, T1 ‐weighted images (T1 WI), and diffusion tensor imaging (DTI) covering the whole brain were acquired with a 3.0T scanner. Assessment: Amplitude of low‐frequency fluctuations (ALFF) in WM and the correlation coefficients between WM and GM were examined and compared among the three participant groups by two reviewers independently. Independent component analysis (ICA) was added to evaluate WM‐fMRI signals. Statistical Tests: Analysis of covariance (ANCOVA); Pearson correlation analysis. Results: Never‐treated patients demonstrated lower ALFF in splenium of corpus callosum (SCC) relative to treated patients and controls ( P < 0.001, false discovery rate [FDR]‐corrected). While the extracted independent component also located in SCC and showed significantly decreased connectivity in never‐treated patients when compared to controls ( P < 0.05, FDR‐corrected). The correlation coefficients of WM‐GM displayed greater reductions in the genu of corpus callosum (GCC), pontine crossing tract (PC), bilateral cingulum (hippocampus) (CGH), and bilateral corticospinal tract (CST) in treated patients relative to controls ( P < 0.05, FDR‐corrected). Data Conclusion: These findings provide new insight into WM functional alterations over the long‐term course of schizophrenia with and without the potential effects of antipsychotic medication. Functional change and abnormal connectivity in SCC were both found greater in untreated patients than treated patients relative to healthy controls, suggesting that long‐term antipsychotic treatment may show some protective effects on WM functional organization. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2020;52:752–763.